FAKTOR YANG MEMPENGARUHI INOVASI PRODUK DAN HARGA PENJUALAN PADA TOKO KELONTONG - Naylal Fithri; Siti Mutmainnah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
Innovation is a word that is familiar to our ears and is key for the business world. Grocery stores also innovate products by producing their own products. This type of research uses quantitative methods, which aim to solve factors that influence the success or failure of grocery store sales caused by the rise of modern retail. Data collection techniques were carried out using population, sample research, data sources and questionnaires with spss 21 calculations. The research results obtained from grocery stores in rawan village were based on product innovation with product quality ( ) with a percentage result of 69% in the medium category indicating that the store grocery hj. Sus does not indicate a high or low category. Meanwhile, the results of price ( ) with a percentage value of 60% in the medium category also indicate that it is not in the high or low category. These results also show that there are difficulties in reaching prices for various products and that there are competitors between grocery stores. Purchase decisions are at a percentage of 54% at the hj store. Sus in rawan village which was reviewed by searching for information, indicators of recognition of various problems according to needs, evaluation of alternatives, buyer decisions and behavior after purchase.